1988
DOI: 10.1128/aac.32.12.1763
|View full text |Cite
|
Sign up to set email alerts
|

In vitro mechanism of inhibition of bacterial cell growth by allicin

Abstract: Diallyl thiosulfinate (allicin) is the agent found in garlic which is responsible for the antibacterial and antifungal activity of extracts of this plant. The effect of bacteriostatic concentrations of allicin (0.2 to 0.5 mM) on the growth of Salmonella typhimurium revealed a pattern of inhibition characterized by: (i) a lag of approximately 15 min between addition of allicin and onset of inhibition, (ii) a transitory inhibition phase whose duration was proportional to allicin concentration and inversely propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
135
0
6

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(145 citation statements)
references
References 27 publications
4
135
0
6
Order By: Relevance
“…The microbial inhibitory action of the findings of Bowels et al (1995) who reported that essential oil of garlic may be due to its antimicrobial cinnamon oil inhibited the growth of Staphylococcus compound, allicin and the effect will be brought about aureus, Helander et al (1998) who observed the by its ability to inactivate proteins (Barone and Tansey, inhibition of Escherichia coli O157: H7 and 1977) and also by inhibition of RNA synthesis Salmonella typhimurium by the essential oil of (Feldberg et al 1988). cinnamon, Friedman et al (2002) coli as the most sensitive and Listeria monocytogenes The minimum inhibitory concentration as least sensitive to the inhibitory activity of garlic, of essential oil of garlic for various bacterial pathogens Arora and Kaur (1999) reported that Staphylococcus are given in Table 2.…”
Section: Introductionmentioning
confidence: 89%
“…The microbial inhibitory action of the findings of Bowels et al (1995) who reported that essential oil of garlic may be due to its antimicrobial cinnamon oil inhibited the growth of Staphylococcus compound, allicin and the effect will be brought about aureus, Helander et al (1998) who observed the by its ability to inactivate proteins (Barone and Tansey, inhibition of Escherichia coli O157: H7 and 1977) and also by inhibition of RNA synthesis Salmonella typhimurium by the essential oil of (Feldberg et al 1988). cinnamon, Friedman et al (2002) coli as the most sensitive and Listeria monocytogenes The minimum inhibitory concentration as least sensitive to the inhibitory activity of garlic, of essential oil of garlic for various bacterial pathogens Arora and Kaur (1999) reported that Staphylococcus are given in Table 2.…”
Section: Introductionmentioning
confidence: 89%
“…This area, mostly run by local small-scale farmers, is famous for its top-quality, fragrance-rich green onions. Green onions and garlic are commonly consumed vegetables that possess markedly bioactive potentials, such as antioxidant capacity [4], antimicrobial activity [5,6], antiplatelet activities [7] and anticancer activity [8]. With successful demonstration of the functioning properties of the Sunshin green onions, this study would help the local farmers to market their produce with value adding strategies and benefit economically from their production.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant and antimicrobial effects of Allium plants have been reported for times [1,4,5,10]; however, a study on the top-quality green onions and garlic produced in Taiwan is still scarce. In this study, different types of tissue of Taiwan Sun-Shin green onion and garlic were extracted from roots, stems and leaves using ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…Garlic (Allium satiVum L.) has long been used as one of the representative vegetables possessing marked pharmacological potentials, such as antimicrobial activity (1,2) and antiplatelet and antithrombotic activities (3-7) as well as anticancer activity (8)(9)(10). Studies on garlic have been reported in more than 3000 papers, which have disclosed that garlic produces many organosulfur compounds depending on the method of cooking, treatment, or preservation (11)(12)(13); these differences result in differences in its biological effects.…”
Section: Introductionmentioning
confidence: 99%